2013
DOI: 10.4236/nr.2013.43029
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of <i>Spartium junceum</i> L. (Fabaceae) Aromatic Water

Abstract: In this study, antimicrobial, antioxidant and cytotoxic activities of Spartium junceum L. aromatic water (SJAW), obtained by vacuum process distillation, were investigated. Antimicrobial activity of SJAW was evaluated against fungal organisms, Gram-positive and Gram-negative bacteria using agar-well diffusion method. Moreover, the ability of SJAW to sensitize Staphyloccus aureus to antibiotics was also evaluated. The antioxidant activity was examined by 2,2'-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…As a result of the test, it was found that the basic components of S. junceum aromatic water were not cytotoxic to the normal NCTC 2544 cells used as controls, whereas it was showed a significant growth inhibitory effect on the RPMI 7932. In this study, although plant extracts were used as material, to be similar to the findings of Cerchiara et al, 15 we determined that methanol and aqueous extracts prepared from S. junceum's flowers and stems have no cytotoxic effect on normal Vero cells. According to the antiviral activity of the extracts, it has been found that all extracts showed different degrees of anti-HSV-1 activity.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…As a result of the test, it was found that the basic components of S. junceum aromatic water were not cytotoxic to the normal NCTC 2544 cells used as controls, whereas it was showed a significant growth inhibitory effect on the RPMI 7932. In this study, although plant extracts were used as material, to be similar to the findings of Cerchiara et al, 15 we determined that methanol and aqueous extracts prepared from S. junceum's flowers and stems have no cytotoxic effect on normal Vero cells. According to the antiviral activity of the extracts, it has been found that all extracts showed different degrees of anti-HSV-1 activity.…”
Section: Resultssupporting
confidence: 75%
“…According to the Rukunga and Simons classification 42 ; Extracts having a CC 50 value of less than 2 µg/mL are cytotoxic, extracts having a CC 50 value between 2-89 µg/mL are partially (moderate) cytotoxic, and extracts having a CC 50 of more than 90 µg/mL are nontoxic. Cerchiara et al, 15 determined chemical composition of aromatic water obtained from S. junceum flowers by using real samples of individual analytes as reference with Solid Phase Micro Extraction / Gas Chromatography / Mass Spectrometry (SPME/GC/ MS), and they performed quantitative measurements of some components by High Performance Liquid Chromatography/Diode Array Detector (HPLC/DAD) method. They were tested the cytotoxic activities of the essential components of aromatic water [(nerolidol, 1-octen-3-ol, farnesene, linalool, lynalyl acetate, and 2,4-bis (1,1-dy-methylethyl) phenol) on melanoma RPMI 7932 and normal keratinocyte NCTC 2544 cell lines by trypan blue dye method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has an anticancer property and cytotoxic property. This compound has been reported as cytotoxic compounds by inhibiting various types of neoplastic cell lines and some of the compounds are potent anticancer agents [35][36] .…”
Section: -Trifluoroacetoxytridecanementioning
confidence: 99%